Kinematics and kinetics comparative analysis of ski jumping during competition and specific training exercise - Pozzo, R.; Rejc, E.; Cotelli, C.; Guerrini, G.; Morandini, F.; Canclini, A. (International Congress Mountain & Sport. Updating study and research from laboratory to field. 11th-12th November 2005. Rovereto (TN) - Italy. Programme and book of abstracts, 2005)
Introduction: Ski-jumping is a complex skill where the athlete should match high ballistic demands and great aerodynamic constrains.Sequence of motion can be divided into the phases approach, take-off, flight and landing. The take-off and flight phase have the greater influence on the length performance (Komi 1997, Virmavirta 2001). Investigations of measurements of differential ground reaction forces between the sole of the foot and ski , from approach to landing have been taken by Schwameder (1995): Kinematic analysis are also documented in the literature (Arndt 1995). The ability of the jumper to perform a skill-full take off, in order to get the best aerodynamic conditions in the early phase of the flight, is of extreme importance for a successful jump. This is due not only by a power oriented execution of the take-off, but also by good "tuning" the position of each body segment according to aerodynamic demands of the flight (body posture). So the movements of the body segment are to be regulated in relation to an external reference system (jumping hill) and to an internal reference system (body posture). Coaches and athletes are interested to understand the relationship between body posture, timing in the angular displacement, equilibrium conditions, pressure on the boots and they often use simulation exercise in order to improve their ability to reproduce the optimal motion pattern. The purpose of this study was to analyse the kinematics and dynamics of ski jumping under normal conditions and during the simulating training exercise for young elite jumpers. Methods: The take-off phase and the early flight phase were video taken with a digital camera (Canon) operating at 50 Hz and positioned perpendicular to the take-off table at 30m distance. A portable system for recording insole pressure distribution (Pedar-Emed) operating at 100Hz was also used. Six to eight young jumper of the Italian national team participated to the investigations. Measurements have been taken during training competition (Predazzo-Planica) and during training simulations on the gym. All subjects were previously informed about the aims of the study. 2-D analysis was performed using a dedicated software (SIMI-Motion) and CG was calculated with 17 segment model (Gubitz).From pressure data, force-time curves and centre of pressure displacement (COP) were calculated for each foot. Results: Fig 1 shows the typical time curve of insole reaction force of both feet during a complete ski jump event (upper graph) and the trajectory path of COP during the take-off phase. Interesting to note that, in this case, the force value are still present during the flight phase. The comparison of the force curve during the approach and the take-off reveal different strategies of load distribution between the feet and within the single foot. Some athletes show a constant predominance of the same leg, whereas other subject change the loading preference between the legs. These subjects often include a different anterior-posterior COP-displacement pattern and present a non symmetrical alignment of the skis with respect to the early phase of the flight. The kinematic data of these jumpers are less stable in their reproducibility especially in the time phase of the angle, and angular velocity curves. Moreover, difference in the horizontal distance of shoulder and knee joint with respect to the ankle joint are correlated to the with voluntary adjustment of posture strategy. When subjects perform the simulation exercise, differences occur between the time-curve of angle displacement with respect the normal jumping conditions. This is habitually the case for those subjects with greater alteration on the symmetry and stability of the force and angular velocity time-curve patterns. Relevant difference are present especially for the ankle joint in the start position and for the angular velocity peak value and time phase of the hip joint. Peak angular velocity were 9,1 rad/s for knee joint and 8,4 rad/s for knee joint which are less than for top level jumpers (Komi 2001). Interesting to note, that high angular velocity in shoulder joint correlate with a less pronounced value in the hip and knee joints. Discussion/Conclusion: Individual strategy in kinematic and dynamic patterns are well documented by means of the implemented analysis tools.This should improve the evaluation model but also the link between coach`s assessment of technique and athletes subjective movement perception.